RESPON SISWA TERHADAP MODUL SISTEM EKSKRESI MANUSIA PADA PEMBELAJARAN BIOLOGI KELAS XI SMA - sari, Desti Puspita; Putri Panjaitan, Ruqiah Ganda; Wahyuni, eKO Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research aims to determine the responses of students to the human excretion system module on learning biology class XI SMA. The form of research is descriptive research with survey method. The sample in this research are the students of class XI SMA consisting of 31 students of class XI MIPA 3 in SMA Negeri 1 Pontianak, 35 students of class XI MIPA 1 in SMA Negeri 7 Pontianak, and 38 students of class XI MIPA 1 in SMA Negeri 8 Pontianak. Instruments are used a student response questionnaire to find out the student's response to the human excretion system module. The response of students classified into three category, namely responses that are cognitive, affective and conative. The students will response questionnaire consists of 14 statements, 7 positive statements and 7 negative statements. The cognitive response reached an average score of 82.1% in very strong categories, affective responses achieved an average percentage of 80% in the strong category, and the conative response reached an average percentage of 76.8 % in strong category. It can be concluded that student’s responses are very strong in the cognitive response category, whereas in the affective and conative responses categories are strong.Keywords: Modules, Student’s Responses, Human Excretion Systems